PENGARUH MERENDAM KAKI DENGAN AIR HANGAT TERHADAP KUANTITAS TIDUR LANSIA DI PANTI SOSIAL TRESNA WERDHA GAU MABAJI KABUPATEN GOWA SULAWESI SELATAN - Fransiska Anita (Jurnal Keperawatan Florence Nightingale, 2018)
Sleep is a basic need that must be met by humans . Sleep disorders can lead to serious problems and even reduce quality of life . This often occurs in the elderly that decrease the quantity of sleep . To overcome sleep disorders , there are several common ways is by handling pharmacological and non pharmacological . The handlers are non- pharmacological one of them is to soak feet in warm water . Therapy soaking the feet in warm water can improve the microcirculation of the blood vessels and vasodilatation causing a relaxing effect , followed by increased secretion of melatonin thereby increasing the quantity of sleep . This study aimed to identify the effect of soaking the feet in warm water to kuantiats elderly sleep in Social Institutions Tresna Werdha Gau Mabaji Gowa regency of South Sulawesi. The study design is a pre-experimental design approach to one group pre-post test design. The population is elderly Elderly Social Institution Tresna gau Mabaji Gowa district in South Sulawesi who experience sleep disturbances and met the inclusion criteria. The sample of 20 respondents and the sampling technique used is Non-Probability Sampling with purposive sampling approach. Of the 20 respondents who researched obtained all respondents experienced an increase in the quantity of sleep. Data obtained through observation sheets using Normal Sleep Quantity Value in the elderly (6 hours / day). Data were analyzed using SPSS with the test used is the paired t test obtained value ? = 0.000 and the value of ? = 0.05 this indicates that ? < ?, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, it means no influence soaking the feet in warm water to kuantiats elderly sleep in Social Institutions Tresna Werdha Gau Mabaji Gowa regency of South Sulawesi.